Study of a Pathological E-Learning via Content Analysis on the Campus of the University of Tehran - Fatemeh Bahrami; Ali Rashidi (Iranian Journal of Educational Research)
Objective: E-learning is one of the most important developments in the information systems industry and radical change, the use of which as a pedagogical tool in education is rapidly expanding. In this research, the process of e-learning in the University of Tehran has been studied and the advantages and disadvantages of the current system have been investigated by the theme analysis method. Methods: The population of this study included all (students-experts) of Farabi Campus of the University of Tehran who were directly and indirectly involved in e-learning. This research was conducted using a qualitative method by conducting semi-structured interviews with 8 randomly selected virtual students of the University of Tehran. In order to analyze the data obtained from the interviews, the content analysis method was used. Results: According to the analysis of the answers provided, the benefits of this training for students in 5 categories (removal of historical-geographical limitations, cost savings, Improving the learning-learning process, high interactivity and finally individual differences). The advantage of this type of training for the educational organization in 4 categories (executive benefits, human resources, economic and educational-developmental) And the problems of this education were summarized by students in 3 general categories (learning problems, security and technology). Conclusions: Finally, it is recommended that officials and managers, by better understanding of the existing problems in the field of e-learning and solving them, can bring this type of education to their desired position in education in terms of quality and quantity.